Maqasid al-Shari’ah and academic programme in the built environment: A case of the Bachelor of Quantity Surveying at IIUM - Ahmad Sarkawi, Azila; Abdul Rashid, Khairuddin; Hasan, Sharina Farihah; Mohamad, Nor Asiah (2015)
The body of knowledge related to the built and natural environments includes architecture, urban and regional planning, land and property management, engineering, quantity surveying, construction technology and landscape architecture. The said body of knowledge appears to be the closest to what would be required in the planning, designing, constructing and managing the Earth as its khalifah. However, the frequent occurrences of floods, pollution, de-forestation, droughts, etc. suggest that man has failed to carry theamanah. Thus, questions such as whether man is in possession of the appropriate knowledge and understanding on how to manage the Earth, in particular, on aspects related to the attainment of the maqasid al-shariahwere often asked. In an attempt to seek answers to this question a study was carried out. In the study the programme structure and course outlines of the Bachelor of Quantity Surveying (BQS) (Honours) offered by the Kulliyyah of Architecture and Environmental Design, IIUM was chosen as a model to represent the knowledge areas for the built environment. By applying the content analysis technique the BQS (Honours) programmewas analysed and contrasted with the five key components of the maqasid al-shari’ahi.e. preservation of (i) faith, (ii) self, (iii) intellect, (iv) lineage, and (iv) property. The output from the content analysis was then presented and thereafter validated via a focus group discussion (FGD) comprising of experts in quantity surveying and the shari’ah.Key findings from the study suggest that the BQS programme at IIUM has, in its contents, embraced all five core essentials of the maqasid al-shari’ah, the highest content appears to be themaqasid al-shari’ah’spreservation of “intellect” followed by “”self”, “property”, “faith” and “lineage”. The outcome implies that graduates of the BQS (Honours) programme at IIUM are having intheir possession the appropriate knowledge and understanding of themaqasid al-shari’ah. This therefore should facilitate them in performing their roles as professionals related to the built environment and as the Earth’s khalifah.